2020
DOI: 10.1016/j.jocn.2020.10.034
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional comparison of performance, neurophysiological and MRI outcomes of responders and non-responders to fampridine treatment in multiple sclerosis – An explorative study

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Another limitation is related to the long acquisition time, which was the main reason for examining the right sciatic nerve only in this pilot study; a common approach in electrophysiological studies in MS is to examine both sides as a reflection of the global affection of the motor pathways (32)(33)(34). However, multi-modal investigations to extract biophysically meaningful imaging biomarkers related to PNS damage are likely to involve even longer acquisitions and this will need to be accounted for in future study designs.…”
Section: Limitationsmentioning
confidence: 99%
“…Another limitation is related to the long acquisition time, which was the main reason for examining the right sciatic nerve only in this pilot study; a common approach in electrophysiological studies in MS is to examine both sides as a reflection of the global affection of the motor pathways (32)(33)(34). However, multi-modal investigations to extract biophysically meaningful imaging biomarkers related to PNS damage are likely to involve even longer acquisitions and this will need to be accounted for in future study designs.…”
Section: Limitationsmentioning
confidence: 99%
“…Motor evoked potential signals to the VM and TA muscles were facilitated by asking the participants to do a slight voluntary knee extension and dorsiflexion of the ankle, respectively. Electroneuronography (ENG) of the peroneal and tibial nerves was performed using a bipolar surface electrode with pulse durations of 0.1 ms. Electrode placements and distances to the stimulation sites were undertaken using a ruler to ensure reproducibility with the methods applied in the baseline study ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the main objectives of this explorative study were to identify if biomarkers, evaluated in a cross-sectional study by Mamoei et al ( 21 ), would remain stable at 1-year follow-up in PwMS with walking impairments, who already were established as responders and non-responders to Fampridine treatment. These biomarkers are applied in the evaluation of disability measures, physical and cognitive performance, neurophysiology, and brain MRI.…”
Section: Introductionmentioning
confidence: 99%
“…in persons with MS, yet the pattern of results was heterogenous. Several studies reported no significant associations among neuroimaging and mobility outcomes [23,37,49,61], while some studies reported concurrent associations among specific neuroimaging and mobility outcomes along with no associations among other neuroimaging and mobility outcomes [35,38,39,45,46,[50][51][52]54], as well as cases wherein separate studies reported opposing results [23,24]. Further, there was minimal replication of results such that multiple studies reported different findings using different methodological approaches.…”
Section: Roi: Hippocampusmentioning
confidence: 99%